(3GdNjQGJ GdMSGf aj JaSjQ GdbQBfs - (3eMeO QVG Hf bGSe Hf eMeO GdZQGhj, J (B1385(3g` (B1965(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf HGQF GdNdGFb CLeYjf (B... (3ebOeI GYde Cf GdcdGe aj GdGSJOdGd Ydi KHhJ GdeWdhH deG cGf eJhba Ydi KHhJ YUeJge (B... (3GdeWdH GdChd GYde gOGc Gddg Cfg jLH aj GdEeGe Gf jchf eYUheGs
(3BNQgG (B:s
(3BNQgG(B: (3ShQI GdaJM fRdJ aj MLI GdhOGY GYdGeG dg Udi Gddg Ydjg hSde HOfhG CLdg MJi jfUH YdeGA GdfGS ef HYOg hEeGeGege HQZe GdefGabhf, ShQI JHJ fRdJ aj CHj dgH hGeQCJg Ce Lejds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3GdPQjYI, L (B7: 203s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs